Changes in retinal nerve fiber layer thickness after acute primary angle closure - Aung, Tin; Husain, Rahat; Gazzard, Gus; Chan, Yiong-Huak; Devereux, Joseph G; Hoh, Sek-Tien; Seah, Steve K.L (Ophthalmology (Rochester, Minn.), 2004)
To evaluate the changes in retinal nerve fiber layer (RNFL) thickness in the first 16 weeks after acute primary angle closure (APAC) using scanning laser polarimetry (SLP). Prospective, observational case series. Thirty-seven Asian subjects with APAC. For all cases, APAC had resolved after treatment, and the study was conducted during the follow-up period after the acute episode. Using the GDx Nerve Fiber Analyzer (Laser Diagnostic Technologies, San Diego, CA), the RNFL was assessed in both eyes 2 weeks after APAC, and again after 16 weeks. The SLP parameters were compared between week 2 and week 16 within affected and fellow eyes. A multiple logistic regression analysis was carried out to analyze factors likely to influence RNFL outcome. Superior and inferior average RNFL thickness. The mean age of study subjects was 60.1±10.3 years (range, 46–91 years), and most subjects were female (68%) and Chinese (86%). In APAC eyes, the superior average RNFL thickness decreased from 63.8±13.6 μm to 61.4±11.2 μm ( P = 0.04) and the inferior average RNFL thickness decreased from 69.5±14.4 μm to 66.3±12.6 μm ( P = 0.005). There was also a decrease in inferior ratio ( P = 0.008) and ellipse modulation ( P = 0.02). In the fellow eyes, there was no difference found between week 2 and week 16 for any of the SLP parameters studied. Logistic regression analysis showed no significant association between developing a 10% reduction in either superior or inferior RNFL thickness with age, gender, history of ischemic risk factors, duration of symptoms during APAC, the level of presenting intraocular pressure (IOP), or the development of a rise in IOP between study visits. After an episode of APAC, superior and inferior average RNFL thickness was found to decrease significantly from week 2 to week 16.